Comparison Between Sagulubbeg And Madobag Dialect In Mentawai - Raflis, Raflis; Hijon, Hijon (Jurnal Ilmiah Langue and Parole, 2024)
This research is entitled Comparison between the Sagulubbeg and Madobag dialects in Mentawai. Social Dialect Studies aims to analyze similarities, changes and differences in language dialect forms. The Sagulubbeg and Madobag languages ​​are spoken by the people of Sagulubbeg and Madobag villages as well as Mentawai students at Ekasakti University in Padang. These two languages ​​are tools for everyday communication, but they are different and also have different meanings. The method used in this research is qualitative with a descriptive type, namely describing shapes and forms and calculating the percentage comparison between the Sagulubbeg and Madobag dialects obtained from interviews. The data obtained is in the form of vocabulary from the Sagulubbeg and Madobag dialects in Mentawai. The data collection technique used is an observation technique using the interview method and then transcription is carried out, so that the data can be analyzed according to the research instrument. The theory used in this research is dialect theory. The results of the analysis show that Sagulubbeg is the dominant dialect and Madobag is the contributing dialect with the level of presentation in language dialects of the same form with the same meaning at 40% and dialects of different forms of the language with the same meaning at 60% between Sagulubbek and Madobag. The existence of similarities, changes and differences in form between Sagulubbeg and Madobag dialects in Mentawai is caused by geographical conditions which are the main cause.